2022
DOI: 10.3390/ijerph19031439
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Mental Health Impact on Menstrual Function Aspects: Dysmenorrhea and Premenstrual Syndrome, and Genitourinary Tract Health: A Cross Sectional Study among Jordanian Medical Students

Abstract: The physiology of reproduction is affected by psychological distress through neuroendocrine pathways. Historically, COVID-19 is one of the most stressful events with devastating consequences. This research aims to investigate the relationship between dysmenorrhea, PMS, and reproductive tract health on one hand, and COVID-19-related anxiety, depression, and stress on the other among medical students in Jordan. Medical students were invited through teaching platforms and social media to complete an online survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 57 publications
(76 reference statements)
5
31
0
2
Order By: Relevance
“…In our study, the majority of the participants (66.4%) had no history of prior COVID-19 infection, which is similar to the study of Aolymet et al who reported that 65.2% of their sample population also had no such history [20].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the majority of the participants (66.4%) had no history of prior COVID-19 infection, which is similar to the study of Aolymet et al who reported that 65.2% of their sample population also had no such history [20].…”
Section: Discussionsupporting
confidence: 90%
“…COVID‐19‐associated anxiety was linked to an increase in the severity of dysmenorrhea in women ( p = 0.025) whereas depression caused by COVID‐19 was also linked with worsening dysmenorrhea ( p = 0.008). The incidence and severity of dysmenorrhea increased during the pandemic as 49.9% of the women involved in the study experienced it as compared to 36.9% before the pandemic 21 . This is supported by evidence from another study which shows that out of 125 participants, 22.4% experienced increased menstrual pain during the pandemic as compared to before, and 25.6% of women reported worsening menstrual cycles 22 .…”
Section: Resultsmentioning
confidence: 59%
“…Despite this, 46% of women experienced a change in their menstrual cycle since the pandemic began, compared to 25% before the pandemic (25). In a further experiment conducted in Jorden, 49.9% of 385 female medical students reported severe PMS during COVID-19 compared to before, which was 36.9% (26).…”
Section: The Impact Of Covid-19 On the Menstrual Cycle And Premenstru...mentioning
confidence: 92%